The Intimate Life of Dissent Anthropological Perspectives - Kelly, Tobias (UCL Press, 2020)
The Intimate Life of Dissent examines the meanings and implications of public acts of dissent, drawing on examples from ethnography and history. Acts of dissent are never simply just about abstract principles, but also come at great personal risk to both the dissidents and to those close to them. Dissent is, therefore, embedded in deep, complex and sometimes contradictory intimate relations. This book puts acts of high principle back into the personal relations out of which they emerge and take effect, raising new questions about the relationship between intimacy and political commitment. It does so through an introduction and eight individual chapters, drawing on examples including Sri Lankan leftists, Soviet dissidents, Tibetan exiles, Kurdish prisoners, British pacifists, Indonesian student activists and Jewish peace activists. The Intimate Life of Dissent will be of interest to postgraduate students and researchers of anthropology, history, political theory and sociology. Written in a clear and accessible style, it is also suitable for teaching introductory undergraduate courses on political anthropology.